Valor preditivo dos parâmetros clínicos e dos marcadores biofísicos e bioquímicos, no primeiro trimestre gestacional, na detecção de fetos pequenos para a idade gestacional - Antunes, Irene Reali [UNIFESP] (2020)
Objective: To evaluate the predictive values of maternal characteristics, biophysical parameters (mean arterial pressure [MAP] and Doppler uterine artery measurements), and biochemical parameters (pregnancy-associated plasma protein A [PAPP-A] and placental growth factor [PlGF]) alone and in association for small-for-gestational age (SGA) fetuses, in the absence of pre-eclampsia. Methods: We performed a retrospective analysis of a prospective observational study that evaluated 615 pregnant women in the first trimester using ultrasonography. For all the women, information regarding clinical and obstetric histories, MAP, and uterine artery mean pulsatility index (UtA-PI), and blood samples for analysis of biochemical markers (PAPP-A and PlGF) were obtained. The patients were grouped according to birth weight as follows: group I (n = 571), newborns with weights greater than the 10 th percentile (control); group II (n = 44), newborns with weights lower than the 10 th percentile; and group III (n = 34), newborns with weights lower than the fifth percentile. The predictive values of the variables for the detection of small-for-gestational-age fetuses were calculated using a logistic regression model and an analysis of the area under the receiver- operating characteristic curve (AUC). Results: The sensitivity rates of the maternal characteristics, biophysical markers (MAP and UtA-PI), biochemical markers (PAPP-A and PlGF), and the association between them were: 23.3%, 32.5%, 25%, and 30% respectively, at a false-positive (FP) rate of 10%, in group II and 26.5%, 26.5%, 23.5%, and 23.5%, respectively, at a FP rate of 10% in group III. Conclusions: The predictive performances of the combination of maternal characteristics and biophysical and biochemical parameters were unsatisfactory, with a slight improvement in the predictive capacity for SGA fetuses with weights lower than the 10 th percentile.